1999
DOI: 10.1159/000057465
|View full text |Cite
|
Sign up to set email alerts
|

High Protein/Energy vs. Standard Protein/Energy Nutritional Regimen in the Treatment of Malnourished Hemodialysis Patients

Abstract: Although malnutrition is frequently encountered in maintenance hemodialysis (MHD) patients, a clear method of treating this complication is still lacking. Failure of nutritional support regimens may be due to inadequate support of dietary needs. Therefore, a high vs. standard or low protein/energy dietary regimen was studied in malnourished MHD patients. A total of 18 malnourished MHD patients selected according to subjective global assessment (SGA)-scores and biochemical indicators of malnutrition (serum albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 12 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…To the best of our knowledge, there are 13 randomized controlled trials [104][105][106][107][108][109][110][111][112] of nutritional therapy in ESRD patients. In eight out of the nine randomized trials with serum albumin as a surrogate outcome measure, significant improvement in hypoalbuminemia was reported [104][105][106][107][108][109][110][111][112]. Serum albumin did not increase significantly in the study by Fouque et al [113] but even in this study higher serum albumin and prealbumin levels were observed in those who achieved higher dietary protein intake.…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…To the best of our knowledge, there are 13 randomized controlled trials [104][105][106][107][108][109][110][111][112] of nutritional therapy in ESRD patients. In eight out of the nine randomized trials with serum albumin as a surrogate outcome measure, significant improvement in hypoalbuminemia was reported [104][105][106][107][108][109][110][111][112]. Serum albumin did not increase significantly in the study by Fouque et al [113] but even in this study higher serum albumin and prealbumin levels were observed in those who achieved higher dietary protein intake.…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…Most investigators have shown that serum albumin levels increase during the first six months of dialysis [49][50][51] followed by a decline in values during the second year of maintenance hemodialysis therapy [52]. Results from several small studies have shown that an increase in either energy or protein intake can increase serum albumin levels by 0.5 g/dL to 1.0 g/dL [14,15]. Other interventions in which protein or energy intake were increased did not result in a statistically significant increase in serum albumin levels; perhaps because they involved small numbers of patients and/or they were not randomized trials [2,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of erythropoietin alpha on nutritional status in hemodialysis patients have been well documented, the effects of oral and parenteral supplementation and the correction of acidosis are uncertain [2,[14][15][16][17][18][19][20][21][22][23]. An increased dose of dialysis and the use of biocompatible membranes have also been used to enhance nutritional status in hemodialysis patients.…”
mentioning
confidence: 99%
“…A few studies have reported a possibility of reversing this morbidity and mortality following improvement of the malnutrition state [52,53,54]. To study this effect, investigators infused rhGH at varying doses with primary end points being change in body composition, LBM and other nutritional markers like serum albumin.…”
Section: Evidence For the Use Of Gh In Ckdmentioning
confidence: 99%